Imaging and biopsy of HIV-infected individuals undergoing analytic treatment interruption - Lau, Chuen-Yen; Adan, Matthew A.; Earhart, Jessica; Seamon, Cassie; Nguyen, Thuy; Savramis, Ariana; Adams, Lindsey; Zipparo, Mary-Elizabeth; Madeen, Erin; Huik, Kristi; Grossman, Zehava; Chimukangara, Benjamin; et al. (Frontiers in Medicine, 2022)
Background: HIV persistence during antiretroviral therapy (ART) is the principal obstacle to cure. Lymphoid tissue is a compartment for HIV, but mechanisms of persistence during ART and viral rebound when ART is interrupted are inadequately understood. Metabolic activity in lymphoid tissue of patients on long term ART is relatively low, and increases when ART is stopped. Increase in metabolic activity can be detected by 18fluorodeoxyglucose (FDG)–positron emission tomography (PET) and may represent sites of HIV replication or immune activation in response to HIV replication. Methods: FDG-PET imaging will be used to identify areas of high and low metabolic uptake in lymphoid tissue of individuals undergoing long-term ART. Baseline tissue samples will be collected. Participants will then be randomized 1:1 to continue or interrupt ART via analytic treatment interruption (ATI). Image guided biopsy will be repeated 10 days after ATI initiation. After ART restart criteria are met, image-guided biopsy will be repeated once viral suppression is re-achieved. Participants who continued ART will have a second FDG-PET and biopsies 12 to 16 weeks after the first. Genetic characteristics of HIV populations in areas of high and low FDG uptake will be assesed. Optional assessments of non lymphoid anatomic compartments may be performed to evaluate different reservoir characteristics. Anticipated Results: We anticipate that PET standardized uptake values (SUV) will correlate with HIV viral RNA in biopsies of those regions and that lymph nodes with high SUV will have more viral RNA than those with low SUV within a patient. Individuals who undergo ATI are expected to have diverse viral populations upon viral rebound in lymphoid tissue. HIV populations in tissues may initially be phylogenetically diverse after ATI, with emergence of dominant viral species (clone) over time in plasma. Dominant viral species may represent the same HIV population seen before ATI. Discussion: This study will allow us to explore utility of PET for identification of HIV reservoirs and determine whether high FDG uptake respresents HIV replication. We will also characterize reservoirs in different anatomic locations. Findings will facilitate future targeting of HIV reservoirs and assessment of interventions designed to impact reservoirs.